Politics and constitutions in Southeast Asia - Bünte, Marco; Dressel, Björn (Routledge, Taylor and Francis Group, 2016)
pt. 1. Constitution-making and constitutional design -- pt. 2. Constitutional change and the military -- pt. 3. Constitutions and human rights -- pt. 4. Constitutional politics and the rule of law.
Gesehen am 047.05.2021
Keywords: Südostasien; Electronic books